Ultrasound features of pregnancy‐associated breast cancer: A retrospective observational analysis - Maryam Jafari; Fereshteh Abbasvandi; Elahe Nazeri; Asiie Olfatbakhsh; Ahmad Kaviani; Rezvan Esmaeili (Cancer Medicine, 2023)
Abstract Pregnancy‐associated breast cancer (PABC) is a poor prognosis in women, and the mortality rate is higher in this subgroup of patients than in non‐PABC. This study aims to assess clinicopathological and ultrasound features of patients with PABC. Of 75 patients with breast cancer, 31 cases were in lactating, or pregnancy phase and 44 patients had no recent history of pregnancy/lactation at the time of cancer detection. The available pathological characteristics and ultrasound findings of the PABC and non‐PABC groups were compared. The analysis of ultrasound findings demonstrated that the percentages of antiparallel orientation (p = 0.04) and heterogeneous internal echo pattern (p = 0.002) were higher in the PABC group. The final Breast Imaging Reporting and Data System (BI‐RADS) assessment in the two groups was significantly different (p = 0.008). In this study, most PABCs were BI‐RADS 4c or 5; compared with age‐matched non‐PABC cases. There were significant differences in ER (p = 0.03), receptor groups (p = 0.007), and tumor grade (p = 0.02) in PABC compared to non‐PABC group. To conclude, radiologists should be careful about ultrasound findings of PABC and recommend core needle biopsy in suspected cases.